Numerical investigation of unsteady cloud cavitating flow around the Clark-Y hydrofoil with adaptive mesh refinement using OpenFOAM. (15th June 2020) - Wang, Ziyang; Li, Linmin; Cheng, Huaiyu; Ji, Bin
Abstract: In this paper, the cavitating flow around a three-dimension Clark-Y hydrofoil is investigated by the large eddy simulation (LES) method coupled with the volume of fluid (VOF) model in OpenFOAM. The simulated results are compared with the experimental data and a reasonable agreement is obtained. The cavitation-vortex interaction is studied with the vorticity transport equation and much stronger baroclinic torque term is observed. The adaptive mesh refinement (AMR) method is adopted for improving the accuracy and efficiency of numerical simulation. Comparing with the results presented by the mesh with fine resolution, even the coarse resolution mesh, with AMR method, can precisely characterize identical complex cavity structures and flow details. The local high pressure induced by the reverse flow and small residual vortex structures are obtained by the coarse resolution mesh with the AMR method. Further analyzes of the variation trend of total grid numbers using the AMR in one typical cycle show that the rates of the cloud cavitation shedding and collapse are faster than that of the attached cavity growth. This research illustrates that the AMR is a potential approach to accurately model multi-scale cavitating flows and to better understand cavitation mechanism on the premise of limited computational costs. Highlights: Turbulent attached cavitating flow around a hydrofoil is simulated by LES using OpenFOAM. Adaptive Mesh Refinement (AMR) method is utilized. Cavitation-vortex interaction is discussed with the vorticity transport equation. The simulated results of cavitation shedding process with AMR is demonstrated and evaluated.